2020
DOI: 10.1177/1078155220908946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methotrexate clearance with an enteral urine alkalinization protocol for patients receiving high-dose methotrexate

Abstract: Purpose High-dose methotrexate is a cytotoxic agent used to treat several malignancies. Urine alkalinization with sodium bicarbonate and hyperhydration are given with methotrexate to prevent drug precipitation in the kidneys. Due to a nationwide intravenous sodium bicarbonate shortage, an enteral-based urine alkalinization protocol was instituted. This study compared outcomes and adverse effects between the previously used intravenous and newly implemented enteral protocols. Methods Single center retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…Similar to the results reported by Roy, et al, Kramer et al, and Rouch, et al, this study did not nd a signi cant difference in the rates of renal dysfunction, or mucositis between our PO and IV cohorts [9][10][11]. As well, no difference in the rates of neurologic complications, or hypernatremia were seen.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the results reported by Roy, et al, Kramer et al, and Rouch, et al, this study did not nd a signi cant difference in the rates of renal dysfunction, or mucositis between our PO and IV cohorts [9][10][11]. As well, no difference in the rates of neurologic complications, or hypernatremia were seen.…”
Section: Discussionsupporting
confidence: 91%
“…These adverse effects, however, rarely led to administration issues such as refusal of doses or a need to change sodium bicarbonate formulation. Both Kramer, et al, and Rouch et al found higher rates of diarrhea in their cohorts receiving enteral urine alkalinizing therapy [10,11]. In our study, the rates of diarrhea were similar between our cohorts.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations